Hexagon Contribution Drill Training and Horizontal Swing Training on Table Tennis Skills - liliana Puspa Sari; Dicky Hendrawan; Alan Alfiansyah Putra Karo Karo (Journal Physical Education, Health and Recreation, 2020)
The purpose of this research is to study Horizontal Swing and Hexagon Drill Training on the ability to play table tennis. Experimental research methods. Participants were 12 male students of the SMK Negeri 1 Stabat class who took part in table tennis extracurricular activities. Sampling was done by purposive sampling of 6 students. Purposive Sampling technique was taken because of several considerations namely limited time, energy, and funds so that it cannot take large samples. Considerations in taking samples are old students who take extracurricular table tennis. The study was conducted for 6 weeks with a frequency of exercise 3 times each week. After the data is obtained, then the data is processed using regression analysis techniques. The results of the study that were approved by the Horizontal Swing Exercise on the ability to play tennis students obtained Fcount = 0.14 and Ftable = 7.71, then Fo <from Ftable, the regression conclusion is not significant and there is no Horizontal Swing Exercise exercise on the ability to play table tennis of male students. While Hexagon Drill Training on the ability to play table tennis students obtained Fcount 0.01 and Ftable 7.71 then F0 <Ftabel, the regression conclusion is not meaningful and there is no contribution of Hexagon Drill Training on the ability to play table tennis of male students. The results of the multiple regression assessment of Horizontal Swing and Hexagon Drill Training on the ability to play table tennis for male students of grade 1 at SMK Negeri 1 Stabat obtained Fcount of 0.02 and Ftable of 9.55, thus Fcount <Ftable, no one is expected. table tennis male student class of SMK Negeri 1 Stabat.